Ответ:
Пошаговое объяснение:
1.
1) 5 - 6x = -5x + 1
-6x + 5x = 1 - 5
-x = -4
x = 4
2) 5 - 3x = -7x - 9
-3x + 7x = -9 - 5
4x = -14
x = - 3,5
3) -7 - 4x = -10x - 6
-4x + 10x = -6 + 7
6x = 1
x = 1/6
4) 5x - 3 = 12
5x = 12 + 3
5x = 15
x = 3
5) -x + 9 = 16
-x = 16 - 9
-x = 7
x = -7
2.
1) -(14-21x)=56
-14 + 21x = 56
21x = 56 + 14
21x = 70
x = 3 + 1/3
2) 7(x + 7) = 10x
7x + 49 = 10x
49 = 10x - 7x
49 = 3x
x = 16 + 1/3
3) 3(x + 8) = -3x
3x + 24 = -3x
3x + 3x = -24
6x = -24
x = -4
4) (45 - y) + 8 = 28
45 - y = 20
-y = -25
y = 25
5) 5(x - 5) = -8x + 1
5x - 25 = -8x + 1
5x + 8x = 1 + 25
13x = 26
x = 2
3.
1) (7x + 1) - (9x + 3) = 5
7x + 1 - 9x - 3 = 5
-2x = 5 - 1 + 3
-2x = 7
x = -3,5
2) 3(6x - 1) = 2(9x + 1) - 10
18x - 3 = 18x + 2 - 10
18x - 18x = 2 - 10 + 3
0 = -5
решений нет
3) 4(5x + 2) = 10(2x - 3) + 15
20x + 8 = 20x - 30 + 15
20x - 20x = -30 + 15 - 8
0 = -23
решений нет
4) 2(7x - 7) = 7(2x - 3) + 7
14x - 14 = 14x - 21 + 7
14x - 14x = -21 + 7 + 14
0 = 0
x = любое
5) 3(x + 6) = x + 2(x + 9)
3x + 18 = x + 2x + 18
3x - x - 2x = 18 - 18
0 = 0
x = любое